Beyond tragedy and eternal peace : politics and international relations in the thought of Friedrich Nietzsche - Drolet, Jean-François (McGill-Queen's studies in the history of ideas ;, 2021)
"In Beyond Tragedy and Eternal Peace, Jean-François Drolet provides a synoptic interpretation of Nietzsche's reflections on politics and international relations in the context of the late nineteenth century. Revolving around questions concerning conflict and political violence, the study examines the symbiotic relationship between Nietzsche's critique of Western metaphysics and his analyses of the political processes, institutions and dominant ideologies shaping public life in Germany and Europe during the 1870s and 1880s. This includes the Franco-Prussian War and the unification of Germany under Bismarck, the advent of mass democracy and the rise and transformation of European nationalism. In the German-speaking world, these developments were also central to the emergence of what would come to be known as "Geopolitik" (geopolitics)--a distinct set of intellectual and political initiatives driven by growing anxieties over the more permanent aspects of German political geography and the destabilizing consequences of techno-scientific innovations for world order. Drolet exposes and analyses Nietzsche's account of these developments against the backdrop of Nietzsche's engagement with Kantian thought and "European nihilism"--an all-consuming crisis of meaning triggered by the dissolution of the structuring ideals which had connected the exercise of power with purpose and determined questions of human co-existence under Christianity. Through this reconstructive exegesis, he shows that Nietzsche's philosophy channels a powerful and still greatly under-appreciated account of the changing political processes and agencies that culminated in the momentous collapse of the European society of states during the first half of the twentieth century. "--